Enhanced optoelectronic quality of perovskite thin films with hypophosphorous acid for planar heterojunction solar cells - Zhang, W; Pathak, S; Sakai, N; Stergiopoulos, T; Nayak, P; Noel, N; Haghighirad, A; Burlakov, V; deQuilettes, D; Sadhanala, A; Li, W; Wang, L; et al. (Nature Publishing Group, 2015)
Solution-processed metal halide perovskite semiconductors, such as CH3NH3PbI3, have exhibited remarkable performance in solar cells, despite having non-negligible density of defect states. A likely candidate is halide vacancies within the perovskite crystals, or the presence of metallic lead, both generated due to the imbalanced I/Pb stoichiometry which could evolve during crystallization. Herein, we show that the addition of hypophosphorous acid (HPA) in the precursor solution can significantly improve the film quality, both electronically and topologically, and enhance the photoluminescence intensity, which leads to more efficient and reproducible photovoltaic devices. We demonstrate that the HPA can reduce the oxidized I2 back into I−, and our results indicate that this facilitates an improved stoichiometry in the perovskite crystal and a reduced density of metallic lead.